Enhancing Elementary Students’ Mathematical Achievement in Whole Number Subtraction through the Burning Meatball Interactive Media and Collaborative Learning Approach - Wahyuni, Sri; Wiryanto; Siswono, Tatag Yuli Eko (Papanda Publisher, 2025)
This study aims to investigate the effectiveness of the Burning Meatball interactive media integrated with a collaborative learning approach in improving elementary students’ mathematical achievement in whole number subtraction. Employing a quasi-experimental design with pretest-posttest control groups, the research involved 56 fifth-grade students from two parallel classes in an elementary school. Data on student achievement were collected through tests and analyzed descriptively using percentage scores to determine the improvement in learning outcomes. The results indicate that students taught using the Burning Meatball media combined with collaborative learning achieved a higher percentage increase in learning outcomes compared to the control group. The collaborative learning setting encouraged peer discussion and problem-solving, while the interactive media facilitated better conceptual understanding by visualizing subtraction operations in a fun and engaging way. Analysis of the percentage gain shows that the experimental group experienced a substantial improvement in their performance. These findings suggest that integrating interactive media with cooperative pedagogy can enhance mathematics learning in elementary schools. The study concludes that this approach effectively supports both academic achievement and positive learning attitudes toward mathematics.